2012
DOI: 10.1200/jco.2011.36.4133
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Phase II Trial of Sunitinib on an Intermittent Versus Continuous Dosing Schedule As First-Line Therapy for Advanced Renal Cell Carcinoma

Abstract: Median time to tumor progression was 9.9 months for schedule 4/2 and 7.1 months for the CDD schedule (hazard ratio, 0.77; 95% CI, 0.57 to 1.04; P = .090). No significant difference was observed in overall survival (23.1 v 23.5 months; P = .615), commonly reported adverse events, or patient-reported kidney cancer symptoms. Schedule 4/2 was statistically superior to CDD in time to deterioration, a composite end point of death, progression, and disease-related symptoms (P = .034). CONCLUSION; There was no benefit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
0
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(182 citation statements)
references
References 15 publications
5
169
0
8
Order By: Relevance
“…A recent randomized phase II study comparing a 37.5-mg CDD regimen to the 4/2 schedule (EFFECT trial) demonstrated no differences in drug tolerance or patient-reported symptoms, but showed a trend toward superiority of the 4/2 schedule over CDD in time to tumor progression (9.9 months for 4/2 schedule versus 7.1 months for CDD, HR 0.77, 95% CI 0.57-1.04, P = 0.09). No significant difference was observed in the OS (23.1 months for the 4/2 schedule versus 23.5 months for CDD, P = 0.615) [5].…”
Section: Annals Of Oncology Reviewsmentioning
confidence: 79%
See 2 more Smart Citations
“…A recent randomized phase II study comparing a 37.5-mg CDD regimen to the 4/2 schedule (EFFECT trial) demonstrated no differences in drug tolerance or patient-reported symptoms, but showed a trend toward superiority of the 4/2 schedule over CDD in time to tumor progression (9.9 months for 4/2 schedule versus 7.1 months for CDD, HR 0.77, 95% CI 0.57-1.04, P = 0.09). No significant difference was observed in the OS (23.1 months for the 4/2 schedule versus 23.5 months for CDD, P = 0.615) [5].…”
Section: Annals Of Oncology Reviewsmentioning
confidence: 79%
“…In a study by Wong et al, fatigue and diarrhea were the most troublesome toxicities for patients, and patients were willing to forego 4.4 months of PFS to ameliorate their symptoms from severe to mild-to-moderate [9]. Interestingly, with the standard 4-week treatment followed by a 2-week break, a cyclic scoring pattern is observed in patient-reported quality-of-life indicators; with improvement in mean scores after the 2-week treatment break [5].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Recognition that symptoms recur rapidly during the treatment break might suggest that a continuous regimen might be preferable. Continuous treatment with sunitinib does not seem to have benefits over the 4/2 regimen, 13 so perhaps this patient might be better switched to continuous pazopanib. Alternatively, a patient on pazopanib with cumulative toxicity but a history of a previously slowly growing cancer might find the 2-week treatment break of the 4/2 sunitinib regimen to be a welcome relief.…”
Section: Maximizing Value From Each Therapymentioning
confidence: 91%
“…Klinik çalışmalarda sunitinible tedavi edilen hastalarda GS 18,40 ile 26,40 ay arasında iken, PS 9,90 ile 11 ay arasındaydı. 8,14,29,30 Biz bu çalışmada, ortanca GS ve PS'leri bu klinik çalışmalara göre daha yüksek bulduk. Bu sonuçlara, bizim çalışma grubumuzda hasta sayısının az olması ve bu hastaların çoğunluğunun iyi ve orta risk grubunda olmasının katkısının olabileceğini düşünüyoruz.…”
Section: şEkil 3 Evrelere Göre Genel Sağkalımunclassified